2020
DOI: 10.18203/2394-6040.ijcmph20203009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge among ASHAs in the delivery of contraceptive information and services in coastal Andhra Pradesh

Abstract: Background: Government of India (GOI) is providing comprehensive integrated health care to the urban and rural people under the umbrella of National Health Mission. ASHA as an activist, a village level community health worker acts as an interface between the community and the public health care delivery system, and plays a central role in achieving population policy goals. The aim of study was to assess the knowledge component of ASHAs in the delivery of contraceptive information and services in coastal Andhra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…10 The present study showed that among ASHA workers, only 10% had adequate knowledge regarding NSV which was contrary to another study done in Andhra Pradesh, wherein the knowledge of ASHAs was assessed about contraceptives using a semi-structured interview schedule and it was found that 72.94% of ASHAs had adequate knowledge about contraceptive methods. 8 Also, according to a study conducted in the Surendra Nagar district of Gujarat, it was seen that around 80% of ASHAs had knowledge about NSV which was in contrast with the present study. 11…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…10 The present study showed that among ASHA workers, only 10% had adequate knowledge regarding NSV which was contrary to another study done in Andhra Pradesh, wherein the knowledge of ASHAs was assessed about contraceptives using a semi-structured interview schedule and it was found that 72.94% of ASHAs had adequate knowledge about contraceptive methods. 8 Also, according to a study conducted in the Surendra Nagar district of Gujarat, it was seen that around 80% of ASHAs had knowledge about NSV which was in contrast with the present study. 11…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies 5,6,8,9 showed that non-scalpel vasectomy is an effective family planning method for males and ASHA workers can motivate and ensure greater acceptance towards the same among the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation